The use of intravenous methylprednisolone in giant cell arteritis : a population-based study - Henningson, Hampus; Hammar, Björn; Mohammad, Aladdin J. (Rheumatology, 2025)
Objectives: To determine clinical characteristics, outcome and occurrence of comorbidities in patients with biopsy-confirmed giant cell arteritis (GCA) treated with intravenous methylprednisolone (IVMP) vs those receiving oral glucocorticoids (OGC) only. Methods: A retrospective study included patients with GCA diagnosed from 2004 through 2019. Clinical and laboratory characteristics, and cumulative GC dose were compared in patients receiving IVMP vs OGCs. Changes in visual acuity (VA), occurrence of comorbidities after GCA diagnosis, and mortality were analysed. Results: A total of 419 patients (69% female) were included. In total, 111 patients were initially treated with IVMP, 104 (94%) of whom showed visual manifestations at onset and 308 received OGCs only. Ninety patients (21.5%) exhibited visual involvement at onset, verified by an ophthalmologist. Compared with OGC, patients receiving IVMP exhibited lower inflammatory response at presentation. There was a tendency for improvement in VA with the use of IVMP, but the results were not statistically significant (OR 1.19, 95% CI 0.35–4.01). Patients treated with IVMP had a higher risk of newly diagnosed diabetes mellitus within a year of GCA diagnosis (OR 2.59, 95% CI 1.19–5.63). This risk remained elevated after adjusting for cumulative OGC dose at three months (adjusted OR 3.30, 95% CI 1.29–8.43). There was no difference in survival between treatment groups. Conclusions: Our study found no evidence supporting any benefit of using IVMP in improving VA or survival. IVMP may increase diabetes risk within a year of GCA diagnosis. Further studies are needed to evaluate the value of IVMP in GCA.
Keywords: comorbidities; giant cell arteritis; intravenous methylprednisolone; outcome; survival; visual manifestations